Gastric Emptying and Curding of Pasteurized Donor Human Milk and Mother's Own Milk in Preterm Infants. Issue 1 (July 2015) - Perrella, Sharon L.; Hepworth, Anna R.; Gridneva, Zoya; Simmer, Karen N.; Hartmann, Peter E.; Geddes, Donna T.
<x xml:space="preserve">Abstract</x> ABSTRACT We evaluated the effects of fortification and composition on gastric emptying and curding in un/fortified pairs of mother's own milk (MOM, n = 17) and pasteurized donor human milk (PDHM, n = 15) in preterm infants. Retained meal proportions (%) and curding were determined from sonography. Immediate and subsequent postprandial % were higher for PDHM (23%, P = 0.026; 15%, P = 0.006) and fortified meals (31.5%; 8.8%, both P < 0.001), whereas higher casein, whey, and lactose concentrations were associated with lower immediate postprandial % (all P < 0.006). Curding did not affect emptying. Influences of fortification, pasteurization, and differing breast milk compositions are small and unlikely implicated in preterm feeding intolerance.